Acute postoperative compartment syndrome in a child receiving patient‐controlled analgesia and peripheral nerve block. Issue 1 (8th June 2018) - Ryan, Sarah; Wiseman, Patrick; Mannion, Stephen; O'Sullivan, Michael
Summary: Patient‐controlled analgesia and nerve blocks have been implicated in the delayed or missed diagnosis of acute compartment syndrome. We report a case of early successful diagnosis of acute compartment syndrome in a 15‐year‐old male, who received both morphine‐based patient‐controlled analgesia and a femoral nerve block following corrective surgery for patellofemoral instability. Our case demonstrates that multimodal analgesia, combining both patient‐controlled analgesia and a nerve block, does not necessarily prevent the early diagnosis of an evolving compartment syndrome. There must be a high level of clinical awareness amongst medical and nursing staff regarding the serious potential complication of postoperative compartment syndrome and ongoing vigilance to monitor for its symptoms and signs.